2019
DOI: 10.1016/j.jss.2018.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Different Perspectives on Predictability and Preventability of Surgical Readmissions

Abstract: There is no consensus between readmitted patients and treating doctors about predictability and preventability of readmissions, nor about associated risk factors and root causes. Patients should be more effectively involved in their discharge process, and the relevance of optimal communication between them should be emphasized to create a safe and efficient discharge process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Most studies use the PRISMA-method to focus on the analysis of incidents, unintended events or near-miss events. Similar to Van Galen et al [ 18 ], Cooksley et al [ 19 ] and Fluitman et al [ 17 ], we used the PRISMA-method to gather insight into the root causes of an event, in our study the URP. To our knowledge, the current study is the first study identifying root causes of an URP to the ED with the PRISMA-method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies use the PRISMA-method to focus on the analysis of incidents, unintended events or near-miss events. Similar to Van Galen et al [ 18 ], Cooksley et al [ 19 ] and Fluitman et al [ 17 ], we used the PRISMA-method to gather insight into the root causes of an event, in our study the URP. To our knowledge, the current study is the first study identifying root causes of an URP to the ED with the PRISMA-method.…”
Section: Discussionmentioning
confidence: 99%
“…PRISMA-analysis demonstrated that four (8%) of the readmissions had active (human) related elements. In the study of van Galen et al [ 18 ] patients were asked to qualify their (probable) reasons for readmission into one or more of the five PRISMA categories: 69% of the root causes were disease-related.…”
Section: Discussionmentioning
confidence: 99%
“…In 13 studies, the original ECM was used, and in 12 studies, the ECM was modified because the current ECM did not sufficiently cover the observed types of failures (Table 2). In 4 studies, a new DRF category was added 17–19,29 . The disease-related root cause was first described by Fluitman et al 17 in 2016 and defined as “failures related to the natural progress of disease which are beyond control of patients, their carers and staff.” In these 4 studies, the DRF refers to readmissions and unplanned admissions of patients.…”
Section: Resultsmentioning
confidence: 99%
“… 20 The majority of studies (n = 16) limited the study population to one department or specialty, 14 , 15 , 17 19 , 21 , 22 , 24 26 , 28 , 29 , 32 , 33 , 35 , 36 whereas others included cases from various hospital departments. 19 , 29 , 33 , 36 39 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation